The Mechanism of Action of Follistatin-like Protein-1 (FSTL-1) - V. G. Kukes; Yu. V. Olefir; B. K. Romanov; A. B. Prokofiev; E. V. Parfenova; M. A. Boldyreva; O. A. Goroshko; O. K. Parfenova; A. A. Gazdanova; E. Yu. Demchenkova (Регуляторные исследования и экспертиза лекарственных средств)
The paper provides current data on some proteins of the TGF- p family which are potentially capable of exerting a protective effect in diseases of the heart, lungs, placenta, gonads, and pancreas. The study investigated the anti-inflammatory properties of follistatin-like protein-1 (FSTL-1), one of the proteins of this family, at the cellular level. It was demonstrated that FSTL-1 is responsible for heart muscle regeneration in mammals through activation of angiogenic factors. Despite the fact that this protein plays a key role in myocardial regeneration, its concentration in the epicardium decreases immediately after a heart attack, which hampers effective self-repair of the heart. The paper summarises the results of studies of the efficacy of intravenous administration of FSTL-1 in rats with myocardial infarction. However, the administration of a foreign protein can cause allergic reactions, therefore a drug that induces FSTL-1 secretion was chosen instead.The aim of the study was to provide experimental substantiation of the possibility of exogenous regulation of FSTL-1 secretion.Materials and methods: FSTL-1 concentration in rat plasma was assessed by enzyme immunoassay before and after treatment with the antioxidant drug ethyl methyl hydroxypyridine malate. The antioxidant was administered to 15 healthy male Wistar rats subcutaneously 3 times a day at a dose of 6 mg/day for 14 days. A fasting blood sample was obtained on the first day before administration of the drug and on day 15.Results: after the period of treatment with ethyl methyl hydroxypyridine malate the concentration of FSTL-1 in the plasma of the laboratory rats increased significantly (p = 0.0011) to reach 0.92 ± 0.11 ng/mL as compared to the initial concentration of 0.48 ± 0.04 ng/mL.Conclusion: the study provided experimental evidence for new properties of ethyl methyl hydroxypyridine malate, i.e. induction of FSTL-1 in healthy rats. Further studies are encouraged to assess potential use of this drug as an inductor of FSTL-1 in myocardial ischemia.